An Inka Unku from Caleta Vitor Bay, Northern Chile. Issue 1 (March 2021) - Martens, Tracy; Correa-Lau, Jacqueline; Santoro, Calogero M.; Carter, Christopher; Cameron, Judith
Abstract : As insignia of power and prestige, Inka unku (tapestry tunics) communicated the strength and extent of Inka sociopolitical hegemony in the Andes. Of the 36 known full-size examples in museum collections, only one, found in Argentina, comes from outside Peru. This article investigates another recently excavated unku found out of context on Chile's northernmost coast. To confirm its authenticity, we compiled a database showing the technical and stylistic attributes of previous finds for comparison. We conclude that this artifact is indeed a new type of unku and that the discovery affects our understanding of the complex relationship between the people of this province and the Inka state.